Multifarious Beneficial Effect of Nonessential Amino Acid, Glycine: A Review. (1st March 2017) - Razak, Meerza Abdul; Begum, Pathan Shajahan; Viswanath, Buddolla; Rajagopal, Senthilkumar
Abstract : Glycine is most important and simple, nonessential amino acid in humans, animals, and many mammals. Generally, glycine is synthesized from choline, serine, hydroxyproline, and threonine through interorgan metabolism in which kidneys and liver are the primarily involved. Generally in common feeding conditions, glycine is not sufficiently synthesized in humans, animals, and birds. Glycine acts as precursor for several key metabolites of low molecular weight such as creatine, glutathione, haem, purines, and porphyrins. Glycine is very effective in improving the health and supports the growth and well-being of humans and animals. There are overwhelming reports supporting the role of supplementary glycine in prevention of many diseases and disorders including cancer. Dietary supplementation of proper dose of glycine is effectual in treating metabolic disorders in patients with cardiovascular diseases, several inflammatory diseases, obesity, cancers, and diabetes. Glycine also has the property to enhance the quality of sleep and neurological functions. In this review we will focus on the metabolism of glycine in humans and animals and the recent findings and advances about the beneficial effects and protection of glycine in different disease states.